Evaluation of tourism products as pull factors at Putrajaya Botanical Garden by local visitors - Yahaya, Asmah (2012)
Park visitation is a popular recreational activity among urban residents. The decision to visit a park is related to the park’s attraction as the pull factor. These attractions are related to park’s products such as park’s facilities, services and programmes that enable visitors to enjoy their visit and have memorable experience. In many situations, the lacks of attractive products or recreational opportunities especially in thematic nature park in this country have contributed to the decline in its visitation. Between 2005 and 2009, Putrajaya Botanical Garden faced a similar situation where its declined in visitation could be associated to unexciting product features offered by the park’s management. In this study, an evaluation upon products performance in attracting people to visit the park was conducted. The data were collected through questionnaire survey.Eighteen park attributes were chosen as park attractions or pull factors to determine their relationships with socio-demographic background of visitors and their extent of visitation. It was found that the main source of park’s information was from word-of-mouth and the “park tranquil setting” is the park’s biggest attraction among other attributes. Income and education attainment were identified as the significance factors that contributed to visitation to Putrajaya Botanical Garden. Based on factor analysis, three common pull factors for the park were identified. They were labelled as: “park settings and facilities”, “key visitors’ attractions and services” and “programmes and activities”. Meanwhile, there is a significant correlation between two key factors; i.e., “park settings and facilities”, “key visitors’ attractions and services” and the extent of visitation to the park. The result indicates that as “park settings and facilities” and “key visitors’ attractions and services” as a pull factors increased, the park visitations would also increase. The findings from this study has enabled park management to identify the performance of each park attributes in attracting various segments of visitors to the park. Based on the information, several recommendations have been put forward as mitigation measures in order to sustain visitations and to plan strategies that may improve the frequency of visitations to the park. In addition, the findings have also contributed to increase current understanding of pull factors that influence park visitation to Putrajaya Botanical Garden as thematic nature park.